Accounting for liabilities related to ecosystem degradation - Sue Ogilvy (Taylor & Francis Group, 2018)
Introduction: A growing belief that accounting can and should play a role in halting and reversing degradation of ecosystems is leading to conceptual and methodological developments that recognize the cost of degradation, attribute the cost to the entities responsible and assure that entities can’t ignore the economic burden associated with it. Outcome: Demonstration accounts prepared around a scenario where agricultural use of land includes an obligation to maintain ecosystem condition. The accounts are compliant and coherent with both the international accounting standards for individual entities and the United Nations’ System of Environmental-Economic Accounting. Discussion: Accounting for liabilities for ecosystem degradation demonstrates that, where the liability reflects the lost economic value of the ecosystem, the accounts communicate a reduction in the total net worth of the economy and a redistribution of net worth away from the party responsible for the degradation. The inclusion of both liabilities for degradation and the cost of degradation does not lead to double-counting the economic impact of degradation. Conclusion: Accounting principles and frameworks encourage greater accountability for entities responsible for ecosystem condition by providing greater visibility of the economic cost to individual entities, governments and nations.